Validated model-based simulation tool for design optimization of exploding foil initiators. (April 2015) - Ebenhöch, Stefan; Nau, Siegfried; Häring, Ivo
Exploding foil initiators (EFIs) are highly suitable for use in inline fuze trains containing only secondary high explosives, mainly due to their insensitivity with respect to electromagnetic disturbances or mechanical stress, their precisely controllable fire characteristics and compact size. During EFI operation various multi-physical phenomena occur, such as high-volt switching, foil explosion, generation and acceleration of the flyer plate, as well as shock wave initiation of the explosive by flyer plate impact. In this work all the physical processes, including their coupling, are modelled using multi-physical models that neither employ complex finite elements computations nor experimentally determined fitting parameters. Implemented in a simulation tool, the complete EFI behaviour is covered, from firing (switching) to explosive initiation. Complementary experiments with test structures are conducted, analysing the electrical behaviour and the resulting flyer velocities of different EFI designs. Comparison with these experiments demonstrates the consistency of the simulations and sufficient accuracy. The validated simulation tool is used to determine all-fire/no-fire criteria, to improve geometries and materials and to analyse parasitic influences in the firing circuit. The paper shows that this model-based approach can be used to assess high reliability and safety either for existing or when developing new EFIs.